A comparative study to find out the relationship between the inner inter-canthal distance, interpupillary distance, inter-commissural width, inter-alar width, and the width of maxillary anterior teeth in Aryans and Mongoloids - Mishra, Meena Kumari (Clin Cosmet Investig Dent, 2016)
BACKGROUND: One of the most confusing and difficult aspects of complete denture prosthodontics is the selection of appropriately sized maxillary anterior denture teeth. Various guidelines have been suggested for determining the size of anterior teeth, but different opinions have been reported regarding their significance. In the study reported here, the relationships between facial measurements and the width of maxillary anterior teeth in two ethnic groups, namely Aryans and Mongoloids, were determined. OBJECTIVE: The aims of the study were to determine the inner inter-canthal distance (ICAD), inter-pupillary distance (IPD), inter-commissural width (ICOW), inter-alar width (IAW), and the combined width of maxillary anterior teeth (CW) in Aryans and Mongoloids and to determine the relationships between these measurements. MATERIALS AND METHODS: Impressions of the teeth of 170 dentulous subjects (85 males and 85 females) were made with alginate then Type IV gypsum product was poured in. Measurements of the cast maxillary anterior teeth at their widest dimension (contact areas) were made with the Boley gauge. ICAD, IPD, ICOW, and IAW distances were also measured with a Boley gauge. RESULTS: For all 170 subjects, 85 Aryans and 85 Mongoloids, Pearson’s correlation coefficient (r) for IAW, IPD, ICOW, ICAD, and CW was calculated. In Aryans, highly significant (P<0.001) but weak correlations were found between CW and IAW, IPD, and ICOW. In Mongoloids, a highly significant (P<0.001) and weak correlation was found only between CW and IPD. CONCLUSION: Within the limitations of this study, the results suggest that the IAW, IPD, and ICOW for Aryans and IPD for Mongoloids can be used as a preliminary method for determining the width of the maxillary anterior teeth in edentulous patients.